THE IMPACT OF HYPERURICEMIA ON CARDIOVASCULAR RISK. REVIEW OF THE EXISTING LITERATURE - Mateusz Biszewski; Ida Dunder; Elżbieta Bebrysz; Jan Palmi; Karolina Dębek-Kalinowska; Piotr Bartnik; Jarosław Baran; Magdalena Koss; Aleksandra Drabik; Weronika Ziomek (International Journal of Innovative Technologies in Social Science, 2025)
Objectives: The aim of the current work was to assess, following analysis of existing and widely available literature, whether increased levels of uric acid in blood serum have an impact on increased cardiovascular risk, and is urate-lowering treatment beneficial. Materials and Methods: A review was conducted using the PubMed database, limited to full-text, freely available publications from the past 10 years. The analysis focused primarily on randomized controlled trials, meta-analyses, and systematic reviews related to hyperuricemia and cardiovascular risk. Results: The evidence indicates a consistent association between hyperuricemia and increased cardiovascular risk, including higher all-cause and cardiovascular mortality. Although threshold values for hyperuricemia varied across studies, cardiovascular risk was shown to rise even with levels above 5 mg/dl. SGLT2 inhibitors demonstrated both urate-lowering and cardioprotective effects. In contrast, traditional xanthine oxidase inhibitors (e.g., allopurinol, febuxostat) did not show a significant benefit in reducing cardiovascular events. Conclusions: Hyperuricemia is an independent risk factor for the increase in mortality and other adverse cardiovascular outcomes. SGLT2 inhibitors have shown to be promising in improving cardiovascular prognosis, while xanthine oxidase inhibitors presented no advantages. Further research in this subject is suggested.